PENGEMBANGAN KOMIK BERBASIS KEARIFAN LOKAL DAN PROFIL PELAJAR PANCASILA PADA MATERI GAYA KELAS IV SDN 2 MRANTI PURWOREJO - Purwa ningsih; Yuli Widiyono; Barep Hapit Surya Putra (STKIP Subang, 2026)
This study aims to develop and test the feasibility of comics based on local wisdom and the Pancasila Student Profile on style material for fourth-grade students of SDN 2 Mranti Purworejo. The study uses the Research and Development (R&D) method with the ADDIE model which includes the stages of analysis, design, development, implementation, and evaluation. The subjects of the study were fourth-grade students of the 2025/2026 academic year, consisting of 6 students in the limited trial and 18 students in the broad trial. Data collection techniques included observation, interviews, questionnaires, and pretest and posttest tests. Data were analyzed using a four-point scale percentage to determine the level of feasibility and practicality, while effectiveness was analyzed using the N-Gain score. The results showed that the developed comic obtained a very high level of feasibility, with validation results from media experts of 95%, material experts 84%, and practitioners/teachers 100%. Student responses also showed a very practical category, namely 90% in the limited trial and 91% in the broad trial. The effectiveness test results obtained an N-Gain score of 78.13%, which is considered high. Thus, the comic based on local wisdom and the Pancasila Student Profile is declared highly feasible, practical, and effective for use as a learning resource for the science subject of style in fourth grade elementary school.